2D Nanospace Confined Synthesis of Pseudocapacitance‐Dominated MoS2‐in‐Ti3C2 Superstructure for Ultrafast and Stable Li/Na‐Ion Batteries. (13th August 2018) - Ma, Kun; Jiang, Hao; Hu, Yanjie; Li, Chunzhong
Abstract: Exploring a universal strategy to implement the precise control of 2D nanomaterials in size and layer number is a big challenge for achieving ultrafast and stable Li/Na‐ion batteries. Herein, the confined synthesis of 1–3 layered MoS2 nanocrystals into 2D Ti3 C2 interlayer nanospace with the help of electrostatic attraction and subsequent cetyltrimethyl ammonium bromide (CTAB) directed growth is reported. The MoS2 nanocrystals are tightly anchored into the interlayer by 2D confinement effect and strong MoC covalent bond. Impressively, the disappearance of Li + intercalated into MoS2 reduction peak is successfully observed for the first time in the experiment, showing in a typical surface‐controlled charge storage behavior. The pseudocapacitance‐dominated contribution guarantees a much faster and more stable Li/Na storage performance. As predicted, this electrode exhibits a very high Li + storage capacity of 340 mAh g −1 even at 20 A g −1 and a long cycle life (>1000 times). It also shows an excellent Na + storage capacity of 310 mAh g −1 at 1 A g −1 with a 1600 times high‐rate cycling. Such impressive confined synthesis strategy can be extended to the precise control of other 2D nanomaterials. Abstract : A 2D nanospace confined synthesis strategy is developed for constructing 1–3 layered MoS2 nanocrystals in a Ti3 C2 interlayer. The MoS2 nanocrystals with high surface exposure and rich edges are tightly anchored into the interlayer by a 2D confinement effect and a strong MoC covalent bond, showing a typical pseudocapacitance behavior. Therefore, the MoS2 ‐in‐Ti3 C2 hybrids exhibit ultrafast and stable Li/Na storage.